Possible new application of high-intensity focused ultrasound: degradation of uterine myoma classification - Xueping Peng; Hengxi Chen; Xin Tan; Xiaoli Wang; Jie Liu (International Journal of Hyperthermia)
Hysteroscopic myomectomy is widely used to treat submucosal myomas. However, performing hysteroscopic surgery on certain type II (and even type III) or large myomas remains challenging. High-intensity focused ultrasound (HIFU) has recently emerged as a promising alternative for treating various gynecologic conditions. Studies have shown that following HIFU ablation, not only is the myoma volume reduced, but the intramural portion of the myoma may also protrude into the uterine cavity. This reclassification or ‘degradation’ of the myoma could facilitate the resection of difficult type II and III myomas during hysteroscopy, ultimately reducing the complexity of the procedure and improving surgical safety.